Heavy chain myosin 9-related disease (MYH9-RD): Neutrophil inclusions of myosin-9 as a pathognomonic sign of the disorder - Savoia, Anna; Rocco, Daniela De; Panza, Emanuele; Bozzi, Valeria; Scandellari, Raffaella; Loffredo, Giuseppe; Mumford, Andrew; Heller, Paula G.; Noris, Patrizia; De Groot, Marco R.; Giani, Marisa; Freddi, Paolo; Scognamiglio, Francesca; Riondino, Silvia; Pujol-Moix, Núria; Fabris, Fabrizio; Seri, Marco; Balduini, Carlo L.; Pecci, Alessandro (Thrombosis and Haemostasis, 2010)
MYH9-related disease (MYH9-RD) is an autosomal dominant thrombocytopenia with giant platelets variably associated with young-adult onset of progressive sensorineural hearing loss, presenile cataract, and renal damage. MYH9-RD is caused by mutations of MYH9, the gene encoding for non-muscle heavy-chain myosin-9. Wild-type and mutant myosin-9 aggregate as cytoplasmic inclusions in patients’ leukocytes, the identification of which by immunofluorescence has been proposed as a suitable tool for the diagnosis of MYH9-RD. Since the predictive value of this assay, in terms of sensitivity and specificity, is unknown, we investigated 118 consecutive unrelated patients with a clinical presentation strongly consistent with MYH9-RD. All patients prospectively underwent both the immunofluorescence assay for myosin-9 aggregate detection and molecular genetic analysis of the MYH9 gene. Myosin-9 aggregates were identified in 82 patients, 80 of which (98%) had also a MYH9 mutation. In the remaining 36 patients neither myosin-9 aggregates nor MYH9 mutations were found. Sensitivity and specificity of the immunofluorescence assay was evaluated to be 100% and 95%, respectively. Except for the presence of aggregates, we did not find any other significant difference between patients with or without aggregates, demonstrating that the myosin-9 inclusions in neutrophils are a pathognomonic sign of the disease. However, the identification of the specific MYH9 mutation is still of importance for prognostic aspects of MYH9-RD.
Keywords: MYH9-related diseases; thrombocytopenia; giant platelets; MYH9 gene; neutrophil inclusions